Influence of high altitude on bone age development of children and adolescents - Cidanwangjiu, Tudan'awang, YANG Meijie, Puqiongqiongda, WANG Fengdan, PAN Hui, JIN Zhengyu (Jichu yixue yu linchuang, 2023)
Objective To explore the influence of altitude on the bone growth and development of children and adolescents. Methods From September 2013 to December 2021, children and adolescents with normal development were included from the following regions with three different altitudes:Beijing (Peking Union Medical College Hospital) at 43.5 m above sea level, Lhasa (People's Hospital of Tibet Autonomous Region) at 3 650 m, and Nagqu (People's Hospital of Nagqu and People's Hospital of Nima County) over 4 500 m. Their demographic information and left wrist radiographs were retrospectively analyzed. Assisted by an artificial intelligence bone age (BA) software, a radiologist with 10 years of BA experience interpreted the BA using the Greulich-Pyle method. The differences between BA and chronological age (CA) in different age groups among different altitudes were calculated and statistically analyzed. Results A total of 1 013 participants (671 boys and 342 girls) consisting of 407 Han from Beijing, 456 Tibetan from Lhasa and 150 Tibetan from Nagqu were included. Generally, the BA of children and adolescents in Beijing conformed to the CA, while the average BA of Tibetan children in Lhasa and Naqu lagged behind the CA by 0.50 and 1.33 years, respectively. Compared with those in Beijing, the BA of most age groups (7-18 years old) of Tibetan boys and girls lagged further behind the CA with the increase of altitude. Conclusions The BA of Tibetan children in plateau area lags behind their CA and the gap becomes larger with the increase of altitude.